Structure evolution of nanoparticulate Fe2O3. Issue 7 (14th January 2015) - Erlebach, Andreas; Kurland, Heinz-Dieter; Grabow, Janet; Müller, Frank A.; Sierka, Marek
Abstract : The atomic structure and properties of nanoparticulate Fe2 O3 are characterized starting from its smallest Fe2 O3 building unit through (Fe2 O3 ) n clusters to nanometer-sized Fe2 O3 particles. Abstract : The atomic structure and properties of nanoparticulate Fe2 O3 are characterized starting from its smallest Fe2 O3 building unit through (Fe2 O3 ) n clusters to nanometer-sized Fe2 O3 particles. This is achieved by combining global structure optimizations at the density functional theory level, molecular dynamics simulations by employing tailored, ab initio parameterized interatomic potential functions and experiments. With the exception of nearly tetrahedral, adamantane-like (Fe2 O3 )2 small (Fe2 O3 ) n clusters assume compact, virtually amorphous structures with little or no symmetry. For n = 2–5 (Fe2 O3 ) n clusters consist mainly of two- and three-membered Fe–O rings. Starting from n = 5 they increasingly assume tetrahedral shape with the adamantane-like (Fe2 O3 )2 unit as the main building block. However, the small energy differences between different isomers of the same cluster-size make precise structural assignment for larger (Fe2 O3 ) n clusters difficult. The tetrahedral morphology persists for Fe2 O3 nanoparticles with up to 3 nm in diameter. Simulated crystallization of larger nanoparticles with diameters of about 5 nm demonstrates pronounced melting point depression and leads to formation of ε-Fe2 O3 single crystals with hexagonal morphology. This finding is in excellent agreement with the results obtained for Fe2 O3 nanopowders generated by laser vaporization and provides the first direct indication that ε-Fe2 O3 may be thermodynamically the most stable phase in this size regime.